Habitat heterogeneity influences Odonata (Arthropoda: Insecta) diversity and reveals a new record from Mindanao, Philippines - JOHN LLOYD V. MANANGAN; JUNEL E. OMANDAM; OLGA M. NUÑEZA; REAGAN JOSEPH T. VILLANUEVA (Society for Indonesian Biodiversity, 2026)
Abstract. Manangan JLV, Omandam JE, Nuñeza OM, Villanueva RJT. 2026. Habitat heterogeneity influences Odonata (Arthropoda: Insecta) diversity and reveals a new record from Mindanao, Philippines. Biodiversitas 27 (4): d270402. https://doi.org/10.13057/biodiv/d270402. Sitio Talangisog, an ancestral domain in Misamis Oriental, is one of the remaining dipterocarp forest frontiers in the province and contains a mosaic of interconnected freshwater habitats. This study assessed Odonata assemblages across three sampling sites in each of four habitat types using standardized time-constrained sampling with sweep-netting and handpicking during the dry (January-February 2025) and wet (June 2025) seasons. Systematic sampling recorded 52 species belonging to 12 families and 39 genera. Twenty-four species are endemic, including five of conservation concern: one Near Threatened, two Vulnerable, and two Endangered, notably Drepanosticta clados and Sangabasis bukid. The Asian bronze flutterer, Rhyothemis obsolescens, represents the first confirmed record from Mindanao Island and only the second national record in more than three decades. The most frequently encountered species was Risiocnemis appendiculata (7.12%), while Prodasineura integra occurred in all habitat types. One additional species, the endemic and Vulnerable Indaeschna baluga, was recorded incidentally and excluded from quantitative analyses but reported as a species record. Habitat-averaged diversity indices (n: 3 sites per habitat) were highest in lentic habitats. Bray-Curtis similarity revealed compositional affinity between open and shaded lotic habitats and between lentic and agroecosystems. Distance-based redundancy analysis (db-RDA), supported by non-metric multidimensional scaling (NMDS), showed that environmental variables significantly structured species composition (p: 0.005, adjusted R²: 0.742), with dissolved oxygen, pH, relative humidity, and water temperature identified as significant drivers. Species turnover followed a gradient from warmer, slightly acidic, lower-oxygen waters dominated by generalists in lentic and agroecosystems to cooler, slightly alkaline, well-oxygenated lotic habitats preferred by many endemics. These findings highlight the role of habitat heterogeneity in structuring Odonata communities and emphasize the conservation value of Sitio Talangisog as a refuge for endemic and threatened species.